Nonclassical focal nodular hyperplasia of the liver in a chronic alcoholic: A diagnostic dilemma on FNAC - Pai, R; Khadilkar, UN; Diaz, E; Prabhu, S; Gupta, S (Kathmandu University Medical Journal, 2009)
In a 49 year old male, a chronic alcoholic with hepatomegaly, a subcapsular nodular lesion was detected in the right lobe of the liver. On fine needle aspiration cytology, hepatocellular carcinoma was considered. Excision of the lesion showed features of nonclassical focal nodular hyperplasia with large cell dysplasia that caused the diagnostic dilemma on cytology. Key words: Focal nodular hyperplasia, Large cell dysplasia/atypia, Benign liver mass, Fine needle aspiration cytology doi: 10.3126/kumj.v7i1.1771 Kathmandu University Medical Journal (2009), Vol. 7, No. 1, Issue 25, 76-78